Comparative study between USG and CT scan in the diagnosis of renal stones - Rahman, Selina; Hossain, Faruk; Chowdhory, Md Asif; Rahman, Md Habibur (Bangladesh Medical Journal, 2025)
There is no consensus on which imaging method is more appropriate for people with suspected nephrolithiasis, computed tomography (CT) or ultrasound. In regular clinical practice, ultrasonography can be a useful alternative of CT for evaluating suspected nephrolithiasis, as suggested by the new study. Despite not being as sensitive as CT, USG provides equivalent accuracy while exposing patients to less cumulative radiation and reducing the number of high-risk diagnoses with consequences. This cross-sectional analytical study was carried out from May 2022 to May 2023 in the Department of Urology in collaboration with Department of Radiology and Imaging at Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh to compare the USG and CT scan methods in the diagnosis of renal stone. In this study a total of 206 suspected cases of nephrolithiasis were enrolled initially from outpatient department (OPD), among them 160 cases were primarily diagnosed with renal stones and 46 without renal stones by physical examinations and x-ray. Then 206 suspected cases were scheduled for USG and CT scans to confirm the stone after obtaining consent. A data collection questionnaire was used to record the detailed history of these patients, including USG and CT scan reports. The statistical package for social sciences (SPSS) version 21.0 were used to analyze the data. Study found that male-female ratio was 1.61:1; where male was 61.7%. More than half (54.4%) patients were young/ early adults (21–40 years) and 45.6% of them was in middle age group (41–60 years). Calcium oxalate was the most prevalent type of stone, followed by calcium phosphate (38.1%), cysteine (5.6%), and uric acid (3.8%). Out of 206 suspected cases, 160 patients were accurately diagnosed with renal stones and 46 diagnosed without renal stone. Among the diagnosed renal stone patients 138 were positive and 22 were negative in the USG, with 138 being true positive and 22 being false negative. In 46 patients who were diagnosed without renal stone, 36 were found to be negative and 10 were found to be positive in USG, with these cases being true negative and false positive respectively. Out of the 160 patients diagnosed with renal stones, 148 were diagnosed positive and 12 were negative on CT scan, these were true positive and false negative cases. In 46 patients who were diagnosed without renal stone, 37 were labeled as negative and 9 were labeled as positive on CT scan, these were true negative and false positive cases respectively. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of USG in diagnosis of renal stone were 86.3%, 78.3%, 93.2%, 62.1% and 84.5% respectively. Whereas sensitivity, specificity, PPV, NPV and accuracy of CT scan in diagnosis renal stone were 92.5%, 80.4%, 94.3%, 75.5% and 89.8% respectively. The study found that both imaging modalities USG and CT scan were effective in diagnosing renal stones. However, CT scan results were better, so USG should be considered if CT is not available. Bangladesh Med J. 2024 May; 53(2): 8-12